Counterion Control of t‐BuO‐Mediated Single Electron Transfer to Nitrostilbenes to Construct N‐Hydroxyindoles or Oxindoles. (20th July 2021) - Zhao, Yingwei; Zhu, Haoran; Sung, Siyoung; Wink, Donald J.; Zadrozny, Joseph M.; Driver, Tom G.
Abstract: tert‐Butoxide unlocks new reactivity patterns embedded in nitroarenes. Exposure of nitrostilbenes to sodium tert‐butoxide was found to produce N‐hydroxyindoles at room temperature without an additive. Changing the counterion to potassium changed the reaction outcome to yield solely oxindoles through an unprecedented dioxygen‐transfer reaction followed by a 1, 2‐phenyl migration. Mechanistic experiments established that these reactions proceed via radical intermediates and suggest that counterion coordination controls whether an oxindole or N‐hydroxyindole product is formed. Abstract : tert ‐Butoxide unlocks divergent reactivity embedded in nitrostilbenes to construct N ‐hydroxyindoles or oxindoles depending on whether sodium or potassium is the counterion.